Formulation and In Vitro Evaluation of Nimodipine as an Orodispersible Film - Ghadah Hamid Naji; Khansaa Hattam Abdul-Jabar (Indian Journal of Forensic Medicine & Toxicology, 2021)
The objective of this study is to prepare nimodipine as orodispersible films by using solvent casting methodin order to enhance its oral bioavailability and improve patient compliance. Nimodipine is a calcium channelblocker belongs to class II, it used to improve neurologic outcome following subarachnoid hemorrhage(SAH) by reducing the incidence and severity of ischemic deficits. ODFs were prepared using three typesfilm forming polymers with different concentration HPMC E3, HPMC E5 and HPMC E15, using (Glycerin)as plasticizer and (Poloxamer 407) as surfactant. The effect of different concentrations and types of polymers,on mechanical properties such as (folding endurance and percent of elongation) and the in-vitro evaluationparameters such (disintegration time, surface pH, weight variation and dissolution profile) were evaluated.HPMC E5 films showed slightly higher cumulative % drug release than films of HPMC E3 and HPMC E15at the same concentration of plasticizer and surfactant